ANALISIS PENGARUH KEBIJAKAN DIVIDEN, KEPUTUSAN PENDANAAN, KEPUTUSAN INVESTASI DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - admin, ANDRONIKUS RICKI B1021131104 (Jurnal Manajemen Update, 2017)
Abstract This study aims to analyze the effect of Dividend Policy, Funding Decision, Investment Decision, and Profitability on Firm Value of Manufacturing Company which listed in Indonesian Stock Exchange (IDX). Population of the research are 128 manufacturing companies registered in IDX during 2010-2014 periods. The sample was chosen by using purposive sampling technique and received 21 companies. The results of simultaneous hypothesis test showed a significant effect between independent variables (DPR, DAR, ROA, IOS) on the dependent variable (Tobins Q). Partial results of hypothesis testing showed variable DAR, ROA, and IOS has significant effect on Tobin?s Q, while DPR has no significant effect on firm value. Keywords : Dividend Decision, Funding Decision, Investment Decision, Profitability